Evaluation of open-architecture product adaptability using quantitative measures. Issue 4 (3rd July 2016) - Zhao, Chao; Peng, Qingjin; Gu, Peihua
ABSTRACT: Open architecture provides a sustainable product framework for the mass personalized production with features of adaptability and upgradability. Open-architecture products (OAPs) can support the product change to meet users' requirements in the product life time. A typical OAP would consist of common platforms, add-on modules and public interfaces. The add-on modules include known functional modules at the product development stage and unknown modules to meet the need of the product change in the future. A product open index is proposed in this paper to measure the adaptability of OAPs in their life time. The measures are qualitative for the performance evaluation of OAPs. The evaluation process includes the representation and quantitative measures of product technical factors. Based on the structure of OAPs in product platforms, modules and interfaces, three key technical indicators, namely compatibility of platform, life cycle of modularity, and openness of interface are proposed to evaluate the OAPs adaptability. An industrial painting machine is designed using the open architecture in a case study to verify the proposed method. GRAPHICAL ABSTRACT: